2017
DOI: 10.3174/ajnr.a5059
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Temperature Dysregulation: MR Thermographic Monitoring in a Nonhuman Primate Study of Acute Ischemic Stroke

Abstract: Background and Purpose Cerebral thermoregulation remains poorly understood. Temperature dysregulation is deeply implicated in potentiation of cerebrovascular ischemia. We present a multi-phasic, MR thermographic study in a non-human primate (NHP) model of MCA infarction, hypothesizing detectable brain temperature disturbances and brain-systemic temperature decoupling. Materials and Methods Three rhesus macaque NHP were sourced for three-phase MRI: 1) baseline MRI (t-7); 2) seven-hour continuous MRI following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…Although rectal temperatures predicted and thus could serve as surrogate markers for brain temperatures in SIV‐infected monkeys under the conditions we studied, brain temperatures do not always correlate with peripheral temperature measures . Thus, brain temperature can be a useful independent measure and could be informative in other brain disorders, including in major depression, which is associated with inflammation, as well as in addiction disorders, psychotic disorders, seizure disorders, and stroke …”
Section: Discussionmentioning
confidence: 89%
“…Although rectal temperatures predicted and thus could serve as surrogate markers for brain temperatures in SIV‐infected monkeys under the conditions we studied, brain temperatures do not always correlate with peripheral temperature measures . Thus, brain temperature can be a useful independent measure and could be informative in other brain disorders, including in major depression, which is associated with inflammation, as well as in addiction disorders, psychotic disorders, seizure disorders, and stroke …”
Section: Discussionmentioning
confidence: 89%
“…MR chemical shift thermometry, exploiting the temperature-dependent difference between water and the methyl proton resonance of NAA, was chosen to approximate temperature using an optimized protocol previously reported for phantom as well as human and non-human primate in vivo thermometry. 19, 24, 25, 33 The present study takes advantage of the unique pathophysiologic attributes of chronic cerebrovascular ischemia, in a cohort allowing multiphasic interrogation of a flow-temperature relationship which may not be pragmatic in the clinical acute stroke setting. Ishigaki et al previously reported the use of PET combined with localized, single-voxel MRS-based thermometry to explore the relationship of brain temperature in steno-occlusive disease, observing positive correlations between brain temperature difference (ipsilateral–contralateral hemisphere) with both CBV and OEF.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may in part reflect that baseline brain temperature is inherently a known indicator of diseased tissue energetics, with higher temperature associated positively with hypoperfusion and ischemia. 16, 19, 3638 The benefit of BTR is the ability to quantify a maneuver response, thus producing a form of physiologic contrast with the potential for characterizing not only static tissue impairment, as with baseline brain temperatures, but also the dynamics of the hemodynamic response in a manner similar to CVR. The overall quadratic relationships suggest the presence of multiple regimes of temperature (dys)regulation across the brain determined by additional hemodynamic parameters such as OEF and CMRO 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations